2018
DOI: 10.1111/cei.13181
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circular RNAs hsa_circ_0044235 in peripheral blood as novel biomarkers for rheumatoid arthritis

Abstract: SummaryCircular RNAs (circRNAs) are a new class of RNAs that can be used as biomarkers in clinical blood samples. However, little is known about circRNAs' diagnostic values for rheumatoid arthritis (RA). In this study, the hsa_circ_0054189, hsa_circ_0008675, hsa_circ_0082689, hsa_circ_0082688, hsa_circ_0010932, hsa_circ_0002473 and hsa_circ_0044235 in peripheral blood were determined by quantitative reverse transcription–polymerase chain reaction (qRT–PCR). For hsa_circ_0044235, only one abnormal expression ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 31 publications
0
49
0
1
Order By: Relevance
“…Little research about the role of circRNAs in RA has been conducted. Several recent studies have shown that hsa circ 0044235, hsa circ RNA 104871 and hsa circ RNA 003524 in PBMCs participate in the pathogenesis of RA and can be used as potential biomarkers of RA by microarray analysis [21,22]. In our study, we successfully explored the circRNAs and miRNAs expression profile in PBMCs of RA patients and healthy people using sequencing technology, then evaluated circRNAs expression and circRNA-miRNA co-expression in RA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little research about the role of circRNAs in RA has been conducted. Several recent studies have shown that hsa circ 0044235, hsa circ RNA 104871 and hsa circ RNA 003524 in PBMCs participate in the pathogenesis of RA and can be used as potential biomarkers of RA by microarray analysis [21,22]. In our study, we successfully explored the circRNAs and miRNAs expression profile in PBMCs of RA patients and healthy people using sequencing technology, then evaluated circRNAs expression and circRNA-miRNA co-expression in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with the RNA-seq. A recent study showed that hsa circ 0044235 in PBMCs may be a potential biomarker of RA patients [21]. Another study suggests that increased expression of circRNAs circRNA 104871, circRNA 003524, circRNA 101873 and circRNA 103047 in PBMC from RA patients may serve as potential biomarkers for RA patient diagnosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Following the reactions, the Cq values were determined using the fixed threshold settings. The relative expression levels of Pglyrp1 were calculated using the 2 -ΔCq method normalized to the endogenous control, with ΔCt=Ct target -Ct reference (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are reproducibly and easily detected in clinical blood samples. Stable and enriched circRNAs have been found in peripheral blood [19,20], as well as blood components, such as exosomes [21], plasma [22], platelets [23], erythrocytes [24], and mononuclear cells [25].…”
Section: Discussionmentioning
confidence: 99%